Madagascarhinus, a new genus of the family Siphonorhinidae with two new species from Madagascar (Diplopoda, Siphonophorida) - Wesener, Thomas (Zootaxa, 2023)
Millipedes of the family Siphonorhinidae Cook, 1895, famous for including the leggiest animal on this planet until recently, with up to 750 legs, show a disjunct distribution in California, South Africa and South-East Asia (from India to the Indonesian Islands of Java and Flores). Here I formally describe the first members of the family from Madagascar, Madagascarhinus madagascariensis n. gen., n. sp. and Madagascarhinus andasibensis n. gen., n. sp., from degraded central highland rainforests. Both species of Madagascarhinus n. gen. are relatively short (61 or 63 tergites), setose, pale and slender, and differ from the other known five genera of the family in numerous characters of the antennae, head, and tergites.